Ukrainian postage at the time of the Liberation Struggles in 1918-1920: historical narrative of national stamp publishing - Svetlana Oriekhova (Cхід, 2019)
The article is dedicated to the reconstruction of national historical narratives in light of national stamp publishing. The research is based on the study of the pictorial aspect of the postage stamps of the Ukrainian People’s Republic in 1918-1920 as an expression of state policy towards the development of the national postal service that played an important role in the process of state-building. The diachronic analysis method gives an opportunity to study the process of transformation of postage stamps from the philatelic material to the state of cultural and historical monument. Analytical study of catalogued postage stamps with the general narrative of the past state postal structure of the Ukrainian People’s Republic is defined as the Ukrainian philatelic heritage. Postage stamps as an element of the statehood of Ukraine in the first half of the twentieth century formed the basis of modern national stamp publishing in contemporary narrative of historical memory